Overcoming Ungrievability: Transgender Expectations for Identity after Death. Issue 2 (11th February 2020) - Whitestone, Stephenson Brooks; Giles, Howard; Linz, Daniel
Abstract : Butler ( Precarious Life: The Powers of Mourning and Violence . London, UK: Versa; 2004) observed cultural shifts immediately after 9/11 and suggested that, with regard to grievable and ungrievable lives, societal power structures "produce and maintain certain exclusionary conceptions of who is normatively human" (p. xiv–xv). The current study brings new understanding to the concept of grievability by exploring the symbolically violent de‐transitioning of trans people after their deaths. The aim of this exploratory study was to examine the thoughts and attitudes of older trans people (40 y. o. plus) with regard to the phenomenon of nonconsensual de‐transitioning after death and the expectations they have regarding the expression of their own identity after death. The wishes of the participants were grouped into four outcome categories: hoping to be memorialized only as their lived identity (25%); only as their identity‐assigned‐at‐birth (6%); as both identities combined (44%); and those who claimed that they did not care how their identity was memorialized (25%). Our findings serve to emphasize the importance of open and honest end‐of‐life communication as well as to underscore the diverse nature of the transgender population and the complexity of the transgender identity.